Utilizing appropriate technology for enhancing production and digital marketing of traditional food through a website - Muhamad Azrino Gustalika; Aditya Wijayanto; Riri Irma Suryani (University of Merdeka Malang, 2023)
Serayu Larangan Village in Purbalingga has MSMEs in the form of typical food, namely Jenang and Wajik